Global demand for rice genetic resources - Nelissa Jamora; Venuprasad Ramaiah (CABI Agriculture and Bioscience)
Abstract Background The International Rice Research Institute (IRRI) holds in trust the world's largest collection of rice diversity, with more than 130,000 accessions of cultivated rice and wild species. Between 2012 and 2018, a total of 2174 requests for rice germplasm were received from more than 1000 unique requestors. We documented and analyzed how genebank users made use of germplasm from IRRI. As we address food and nutrition security challenges in a changing context, we are motivated by the need to enhance the conservation, management, and use of rice genetic resources. Methods We examined the patterns of use of the IRRI genebank using distribution data and analyzed the results from a survey of germplasm recipients. The 2019 IRRI genebank user survey is the most recent attempt to obtain structured feedback from genebank end-users in multiple countries on their use of rice germplasm since 1995. We received 244 responses (a 35% response rate) out of the complete list of 694 respondents with valid email addresses. We also tested the relationship between the availability of germplasm information, proxied by the passport data completeness index (PDCI), and the demand for rice accessions, measured by the number of requests for each unique accession using a Negative Binomial regression model. We hypothesized that materials that are better documented are more frequently requested by users because they offer more useful information for targeted research and breeding. Results Between 2012 and 2018, requests for germplasm from outside IRRI were received from 63 countries in all regions of the world, mostly from Asia. IRRI distributed germplasm externally to requestors from universities (32%), national research programs (14%), private companies (9%), and individuals, including farmers (24%) as well as other CGIAR centers (3%). The traits sought most often were tolerances to environmental stresses, followed by tolerance or resistance to biotic stresses. The majority of survey respondents confirmed the usefulness of IRRI germplasm for research, breeding, characterization, and evaluation. The analytical model confirmed the significant positive relationship between PDCI values and the demand for those accessions. The results indicated that improving the availability of information at the accession level will enhance the use of those materials. To the best of our knowledge, this study is the first to show the empirical link between documentation and use of germplasm. Conclusions The findings demonstrate the crucial role of IRRI's genebank as a key germplasm source for global rice research and development, with important implications for the conservation and use of rice genetic diversity in the future. Public sector organizations and the scientific community in general benefit from the conservation and availability of rice genetic resources. We also show the importance of the availability of data on conserved accession to enhance their use. To sustain the benefits, continuous investment in genebanks is needed to allow them to adapt to changes in technology and agricultural context.